Analysing the Impact of the Environment on the Prevalence of Respiratory Diseases in Urban Areas - Korinus Suweni (CV. Get Press Indonesia, 2025)
Urban green spaces have been identified as one of the solutions to improve air quality and reduce the negative impacts of air pollution on respiratory health. This study aims to assess the relationship between environmental factors in urban areas and the prevalence of respiratory diseases, providing evidence-based recommendations for improved environmental and public health policies. Methods. An analytical observational design with a cross-sectional approach was used to evaluate the association of environmental factors, such as air pollution (PM2.5 and PM10), house ventilation, residential density, proximity to main roads, as well as socio-demographic factors (age and education level). Results. The results showed that exposure to secondhand smoke in the home was the most significant risk factor, with respiratory disease prevalence reaching 55%, with an Odds Ratio (OR) = 0.7 and p-value = 0.015, respectively. However, access to green spaces showed protective effects against respiratory disease, confirming the importance of urban planning that supports environmental sustainability.